STRONG CONVERGENCE THEOREMS FOR STRICTLY ASYMPTOTICALLY PSEUDOCONTRACTIVE MAPPINGS IN HILBERT SPACES - Gurucharan Singh Saluja; Hemant Kumar Nashine (Journal of the Indonesian Mathematical Society, 2010)
We propose a new (CQ) algorithm for strictly asymptotically pseudo-contractive mappings and obtain a strong convergence theorem for this class ofmappings in the framework of Hilbert spaces.DOI : http://dx.doi.org/10.22342/jims.16.1.29.25-38